Bacterial meningitis in children admitted in hospitals within Nairobi. - Estambale, Benson B.; Mirza, N B.; Wamola, I A.; Kariuki, N; Onyono, E; Kabiru, P.; Piollet, M. (PubMed, 1998)
Four hundred and ninety nine children (aged between one month and five years) admitted with clinical features of meningitis were recruited in cross-sectional survey of bacterial meningitis in hospitals within Nairobi. Lumbar punctures were done on all of them and the cerebrospinal fluid (CSF) analysed bacteriologically and serologically for the common causative organisms. Two hundred and fifty (50.1%) cases were diagnosed clinically as having meningitis. Of these, 132 (52.8%) had turbid CSF specimens, while 118 (47.2%) were clear. When turbid CSF specimens were cultured, 83 (62.8%) yielded three common bacterial micro-organisms namely; Neisseria meningitidis, Streptococcus pneumoniae and Haemophilus influenzae in that order of frequency. The implications of these findings in paediatric meningitis together with the drug sensitivity patterns is presented and discussed.